Peningkatan Karakter Disiplin Siswa Melalui Penanaman Nilai-Nilai Religius pada Siswa Kelas X SMK PGRI 1 Kota Blitar - Khoirul Muhtarom; M. Irmawan Jauhari; Zaenal Arifin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study aims to improve students' disciplinary character through the instillation of religious values at SMK PGRI 1 Blitar City using a Classroom Action Research (CAR) design consisting of two cycles (Planning, Acting, Observing, and Reflecting). The subjects were 40 students of Class  X at SMK PGRI 1 Blitar City. Data were collected through behavioral observation sheets, questionnaires, and documentation, then analyzed using qualitative and quantitative descriptive methods. The results showed a significant improvement in students' disciplinary character across cycles. In Cycle I, the percentage of students demonstrating high discipline reached 62,5%, which further increased to 87,5% in Cycle II. The key factors driving this improvement were habituation of daily religious routines, teacher role modeling, and integration of religious values into classroom culture. Thus, instilling religious values effectively enhances students' disciplinary character